Malaysian rural ESL students critical thinking literacy level: a case study - Umar Baki, Nurshila; Rafik-Galea, Shameem; Nimehchisalem, Vahid (Australian International Academic Centre, 2016)
In recent years, there has been much interest in the development of thinking skills in the education circles in Malaysia. Nevertheless, more effort needs to be placed on providing skills in developing the critical thinking literacy level of English as a second language (ESL) secondary school students, and its implication on the practice of teaching and learning. This is especially so for rural secondary school students. This paper presents findings of a preliminary case study which analyzes the critical thinking literacy level of twenty students of a rural secondary school in Malaysia as measured by the Cornell Critical Thinking Test (CCTTX). Overall, the findings show that students struggled to answer the critical thinking questions posed in the CCTTX. The analysis point to the fact that students encountered problems with questions on ‘judging what is assumed in an argument’ section of the standardized critical thinking test. Interview responses from students revealed that they found the 71-item-test challenging to answer. Despite the national education agenda to develop world-class thinkers, our study suggests that there appears to be a lack in exposure to thinking-based activities in Malaysian classrooms.